The professional training of future specialists for Industry of hospitality in the United States of America. - Vindyk A.V (Kharkov National Pedagogical University, 2010)
The analysis of the USA's scientists publications on the professional training of specialists of hospitality is presented. The couteuts of curricula of Conrad Hilton's college, University Johnson and Wales has been analyzed. It is found out that the feature of training future specialists for Industry of hospitality consists in close connection with a society, enterprises. The associations of hotels take part in the discussion, adjustments of curricula, quality determination of training of graduating students, giving grants to higher educational establishments of hospitality.